Recent Progress in the Utilization of Silver Nanoparticle and its Derivatives as Photocatalyst: a Mini Bibliometric Study - R.M. Zahrah; M. Norsuria; M.N. Natashah; I.S.M. Binti; Y. Nurfina (Archives of Metallurgy and Materials)
The narrow bandgaps of silver nanostructure and its derivatives make them photocatalytic-efficient. This bibliometric examines silver nanoparticle research in photocatalysis to identify its growth, research gap, and trends. The 1,941 Web of Science Core Collection publications from 2018 to 2023 were used as research data. The search used Publish or Perish, and the investigation was established on topic area with titles, abstracts, keywords, and terms co-occurrence in the study of silver-based photocatalyst. The visualisation was done with VOSviewer. The number of papers on silver nanoparticles and their derivatives as photocatalysts fluctuated, peaking in 2019. The publications focused on visible-light-irradiated photocatalysts. These findings also revealed a research gap that can be filled by studying silver derivatives including silver chloride, silver oxide, silver sulfide, and silver iodide. This bibliometric study should help researchers examine silver nanoparticles in photocatalysis.